Crossover of positive and negative magnetoconductance in composites of nanosilica glass containing dual transition metal oxides. Issue 26 (30th April 2021) - Samanta, Subha; Maity, Anupam; Chatterjee, Alorika; Giri, Saurav; Chakravorty, Dipankar
Abstract : Magnetoconductance swithching phenomenon in nanosilica glass containing dual transition metal oxide ions. Abstract : A facile sol–gel approach to prepare composites of nanosilica glass containing dual transition metal oxides with compositions x CoO·(20 − x )NiO·80SiO2 comprising x values 5 (NC-1), 10 (NC-2) and 15 (NC-3) within hexagonal pores of SBA-15 template has been demonstrated. The synergistic effect of dual transition metal oxide ions on MD properties and crossover of positive and negative magnetoconductance phenomena were observed in these nanocomposite systems. The physical origin of magnetoconductance switching is explained based on the factors: nanoconfinement effect, wave-function shrinkage and spin polarized electron hopping. DFT calculations were performed to understand the structural correlation of the nanoconfined system. The static (dc) and dynamic (ac) responses of magnetization revealed the spin-glass behaviour of the investigated samples. Both scaling law and Vogel–Fulcher law provide a satisfactory fit to our experimental results which are considered as a salient feature of the spin-glass system. Our studies indicate the possibilities of fabricating magnetically controlled multifunctional devices.